When boundaries are blurred: infrastructure needs in support of the climate displaced - Best, Kelsea; Niemeier, Deb; Hadden, Jennifer (Frontiers in Climate, 2025)
Interactions between climate change and human displacement are complex, yet it is clear that climate change has and will continue to alter patterns of mobility. This is true for both trans-border displacement and internal displacement within country borders. Very little attention has been given to the infrastructure needed to support the climate displaced during their journey as well as in communities where they may pause or settle. In contrast to the climate displaced, reasons for refugee flight can range from deprivation, poverty, war, or disasters, and the statutory definition of refugee entitles them to the protection and assistance of the United Nations. This definition does not currently apply to those who move or are displaced because of climate change, though their displacement is no less perilous or traumatic than those protected under the UN Refugee Convention. Regardless of the legal status, engineers are largely absent from conversations about how to support and protect those undergoing displacement from climate change. In this paper, we draw on the general literature of forced displacement and the existing legal processes for refugees to explore the stages in climate-related displacement. We propose a framework for understanding the basic infrastructure needs during four phases: initiation, mobilization, pause and settle. We identify critical infrastructure to support the climate displaced for each of these phases, calling out those aspects of the displacement process in which greater understanding of how engineers can contribute to protection of human rights is needed.